Bimbingan Dan Pendampingan Pengembangangan Bahasa Arab Santri Pondok Pesantren Al-Ihlas Averroes Nepen Krecek Badas Kediri - Ilham; Ahmad Asfi Burhanuddin (LP3M IAIFA Kediri, 2021)
Arabic is a special language because it has a close relationship with Islam. Arabic is very important for Muslims because the Quran and Hadith came down with it. It can be felt that the close relationship between Islam and Arabic brings great advantages to Arabic, both in terms of the existence of Arabic and its grammatical knowledge. In the Qur'an and Hadith, there are many explanations regarding the importance of learning Arabic so as not to be misguided when understanding and practicing it or spreading its Shari'a. The recent phenomenon is the emergence of many teachings that make people confused. If we do not understand Arabic then we will easily believe in new teachings that are not in accordance with the Qur'an and Sunnah. And the many false hadiths and someone who reads the origin of a book without knowing Arabic knowledge. Thus, in this case the author provides guidance and assistance in the development of Arabic language for students at the Al-Ihlas Averroes Islamic boarding school to make it easier for students to understand the Qur'an and Hadith and other religious sciences. This guidance and assistance is sufficient to help students in listening, reading, writing, and speaking Arabic skills. starting from the guidance of Nahwu and Shorof and Hiwar/Muhadatsah with everyday vocabulary. In the process of guidance and assistance in developing the Arabic language, it is very necessary to have the enthusiasm of students and the surrounding community in making the activity a success.